Performance of off -Season Mulberry Cuttings under IBA Treatments - Kumar, Sunil; Kumar, Sudhir (Indian Journal of Agroforestry, 2020)
An experiment was conducted in the nursery of Grassland and Silvopastoral Division at Central research Farm of Indian Grassland and Fodder Research Institute, Jhansi to see the effect of IBA concentrations on different type of mulberry cuttings during off-season (May, 2001). From the study, it was found that hardwood cutting did better over semi hard and soft wood cuttings in respect of survival, shoot length, and number, length and fresh weight of adventitious roots when treated with 500 ppm IBA concentration. The study also revealed that mulberry cuttings could be propagated during off season.